Breaking Up the Logjam : Automated Customs Risk Management System Implementation in Georgia - Beruashvili, Natalia; Mcgill, Olin (World Bank, Washington, DC, 2012)
How do you turn a confusing tangle of red tape into a smooth operation? In Georgia, the solution involved risk management, automation, and a good mechanism for public-private dialogue. This customs reform was a key component of the trade logistics reform introduced by the Government of Georgia and supported by the United States Agency for International Development (USAID) Georgia Business Climate Reform (GBCR) Project, implemented from September 2005 to August 2009. This smart lesson captures some of what made this project a success.